The Social Abandonment of Ancient Urban Settlements, The Case of Ksar Khanguet Sidi Nadji in Biskra, Algeria - Kebbour, Akram; Bouzaher, Soumia; Nasri, Manel; Aibeche, Oumnia (Indonesian Journal of Social Science Research, 2024)
Heritage assets form the substratum and foundation of sustainable development. They bear witness to a past specific to each population, a way of life, systems of behaviour, traditions and specific arts. These witnesses ensure the maintenance, if not the emergence, of identity and the creation of a symbiosis between the traditional and the mod-ern.However, in this particular case, cultural wealth has fallen victim to neglect, the passage of time, indifference and standardisation. The Ksar of Khanguet Sidi Nadji, which is the subject of this research, is suffering from the development of neighbouring towns. Under the in-fluence of social changes, it is being emptied of its population in search of better, more modern living conditions. The aim of this paper is to identify the main reasons for the aban-donment of this ancient urban settlement by its inhabitants. It also highlights the social causes of the changes in the way people use the Ksar today.